Penilaian Efektifitas Pemanfaatan Taman Tirto Agung Dan Taman Pandanaran Kota Semarang - Arif Wirawan (Journal on Education, 2023)
City development occurs rapidly along with increasing population growth. The existence of the park is currently a good step in achieving good environmental quality. Parks need to be supported with various aspects, starting from the availability of complete facilities, playgrounds that meet standards, and good access to parks. This research aims to determine the effectiveness of using Tirto Agung Park and Pandanaran Park, Semarang City. This type of research is quantitative research. Data collection techniques through observation, surveys, and questionnaires. Data analysis is a quantitative analysis by carrying out normality and multicollinearity tests. This test is used to see the effectiveness of the park using discriminants which function to determine the influence and magnitude of the park's effectiveness. The results of this research concluded that the effective value of Pandanaran Park was 60% and very effective at 40%, while the effective value of Tirto Agung Park was 46.9% and very effective at 53.1%. These findings show that Tirto Agung Park and Pandanaran Park are effective, but there is a need to add and improve facilities in these parks. Tirto Agung Park requires shelter, and organizes arts and cultural activities, as well as park maintenance, while Pandanaran Park needs to provide parking, places to eat and drink, shelter, and well-functioning facilities. toilets and drinking water that function well.